Mitofusin 1 and 2 regulation of mitochondrial DNA content is a critical determinant of glucose homeostasis - Vaibhav Sidarala; Jie Zhu; Elena Levi-D’Ancona; Gemma L. Pearson; Emma C. Reck; Emily M. Walker; Brett A. Kaufman; Scott A. Soleimanpour (Nature Communications, 2022)
Sidarala et al. examine the importance of the mitochondrial structural proteins, Mitofusins 1 and 2 (Mfn1/2), in diabetes. They find that Mfn1/2 control blood glucose by preserving mitochondrial DNA content, rather than mitochondrial structure.